2015
DOI: 10.1007/s10534-015-9863-7
|View full text |Cite
|
Sign up to set email alerts
|

Structural evidences for a secondary gold binding site in the hydrophobic box of lysozyme

Abstract: A new crystal structure is reported here for the adduct formed in the reaction between NH4 [Au(Sac)2], AuSac2, a cytotoxic homoleptic gold(I) complex with the saccharinate ligand, and the model protein hen egg white lysozyme. To produce this adduct, AuSac2 breaks down and releases both saccharinate ligands. The resulting Au(I) ions bind the protein to ND1 and NE2 atoms of His15 but also to SD atom of the zero-solvent accessible Met105 side chain, which is located in the protein hydrophobic box. The unexpected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…Thus, the two investigative approaches, applied independently, again provided a very consistent and exhaustive picture for adduct formation. Similar results were obtained using other gold(III) compounds, belonging to the same series, and under different experimental conditions, and even using gold(I) compounds …”
Section: A Joint Esi Ms and Xrd Strategy: Some Relevant Examplessupporting
confidence: 86%
See 1 more Smart Citation
“…Thus, the two investigative approaches, applied independently, again provided a very consistent and exhaustive picture for adduct formation. Similar results were obtained using other gold(III) compounds, belonging to the same series, and under different experimental conditions, and even using gold(I) compounds …”
Section: A Joint Esi Ms and Xrd Strategy: Some Relevant Examplessupporting
confidence: 86%
“…The second ligand of the linear gold(I) center is invariantly ac hloride ion, particularly abundant in the specific crystallization buffer. [16] Thus,t he two investigative approaches, appliedi ndependently,a gainp rovided av ery consistent and exhaustive picture for adduct formation.S imilar results were obtained using other gold(III) compounds, belonging to the same series, [17] and under different experimental conditions, [18] and even using gold(I) compounds. [16] Thus, through the above examples, we have demonstrated the feasibility and effectiveness of the proposed hyphenated approach.…”
Section: Aj Oint Esi Ms and Xrd Strategy: Some Relevant Examplessupporting
confidence: 54%
“…However, it was previously demonstrated by X-ray crystallography that Au(I) ions can coordinate solvent exposed His [50][51][52][53] , also in the presence of free thiols. It has been also shown that Au(I) can bind also Gln side chains, although with lower affinity than that exhibited for Cys, Met and His residues 54 .…”
Section: Reaction Between the Gold N-heterocyclic Carbene Compound Aumentioning
confidence: 99%
“…Indeed, metal ion Au(I) is a soft metal center, demonstrating a strongly pronounced affinity toward soft ligands such as thiols of cysteines and thioethers of methionines [15] and even more with selenols of selenocysteine residues [16]. Nevertheless, several X-ray crystallographic studies proved that Au(I) ions are able to bind solvent-exposed His [17,18] even when free thiols are available. Moreover, Au(I) complexes may bind the Arg and Lys side chains as well as the N-terminal of Ala [19], albeit in the absence of available cysteines, methionines, and histidines.…”
Section: Computational Studies Of Au(i) Metallodrugsmentioning
confidence: 99%